The influence of yak casein micelle size on rennet‐induced coagulation properties. (18th August 2020) - Zhang, Yan; Ren, Fazheng; Wang, Pengjie; Liang, Qi; Peng, Yun; Song, Li; Wen, Pengcheng
Abstract: BACKGROUND: Yak milk formed stronger rennet‐induced gels if the milk contained smalled casein micelles and a higher concentration of calcium. Also casein gels could formed after a shorter incubation time if the milk contained smalled casein micelles. The objective of this study was to estimate the importance of yak casein micelle size on rennet‐induced coagulation properties. RESULTS: Three fractions of different‐sized, undamaged casein micelles ( Ф 112.17 ± 0.83 nm, Ф 207.13 ± 0.59 nm and Ф 269.37 ± 2.89 nm) were obtained by ultracentrifugation. The smallest casein micelles had the highest concentrations of calcium (803.21 ± 8.49 mM), phosphate (445.52 ± 10.66 mM), and κ ‐casein/total casein (19.45%). Rheological analyses determined the optimal gelation times of small, medium, and large casein micelles to be 9.5 ± 0.5, 10.8 ± 0.5, and 13.3 ± 0.2 min, respectively. Higher κ ‐casein concentration in the small casein micelles appeared to facilitate their shorter incubation time. Both the faster caseinomacropeptide (CMP) release rate and rennet‐induced aggregation rate of small casein micelles contributed to a faster change in turbidity. Furthermore, small casein micelles had the highest elastic modulus (G′, 73.21 ± 4.5 Pa) 60 min after the addition of rennet. This was consistent with micro‐photographs, which showed that small casein micelles could form a more homogeneous gel, which had smaller pore sizes. Trial cheese manufacture verified that yak cheese containing small casein micelles, formed curd faster and the cheese had higher texture profile analysis (TPA) values for hardness, cohesiveness, and springiness. CONCLUSION: This is important information for the optimization of yak cheese industrial production. © 2020 Society of Chemical Industry